Development and Validation of a Medicinal Plant Inventory Booklet as an Effective Biodiversity Teaching Material - Nur Amaliah; Ismira Wandira; Gaby Maulida Nurdin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This research and development study aimed to produce a booklet on medicinal plant inventory as an alternative teaching material for biodiversity topics, and to evaluate its validity, practicality, and effectiveness. The development process employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Product testing was conducted on a limited scale involving 19 tenth-grade science students and one biology teacher at SMAN 3 Kalukku. Validity data were obtained from assessments by material and media experts, practicality data were derived from teacher and student questionnaire responses, and effectiveness data were measured through students’ cognitive learning outcomes and skill assessments. The results showed that the booklet achieved a validity score of 4.42 (valid) and practicality scores of 98% for teachers and 88.3% for students. Effectiveness was indicated by cognitive mastery and skill performance scores of 68.4% and 67.36%, respectively (both at the moderate level). This study implies that the developed booklet can help integrate local biodiversity knowledge into learning, thereby supporting more contextually and meaningfully grounded science education.